2020
DOI: 10.1002/jrs.6026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the SERS‐based strategy in fast and on‐site food safety inspection: Qualitative and quantitative analysis of trace unexpected herbicide in complicated herbicide matrix

Abstract: Recently, surface-enhanced Raman spectroscopy (SERS)-based detection strategies have been widely developed for various practical applications, due to the near-single-molecule sensitivity and fingerprint identification capability. However, the qualitative and quantitative reliability of SERS have always been questioned when comparing with the classical GC/LC-MS techniques. Here, we systematically compared the properties of SERS and LC-MS in the detection of an unexpected herbicide in commercial herbicide. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Besides, Listeria monocytogenes was intensively studied by researchers (Anast et al 2020;Kawacka et al 2020;Wu et al 2020b). Another common word was analysis, such as analysis of herbicide (Pan et al 2020), analysis of bacteria (Kang et al 2020), and analysis of microplastics (Primpke et al 2020). Other common research topics revealed by title analysis included but are not limited to food quality, food production, food processing, food additive, food contamination, detection of food contaminants, food microbiology, environmental impact, as well as water, soil, animal, fish, meat, and dairy.…”
Section: A Scientometric Reviewmentioning
confidence: 99%
“…Besides, Listeria monocytogenes was intensively studied by researchers (Anast et al 2020;Kawacka et al 2020;Wu et al 2020b). Another common word was analysis, such as analysis of herbicide (Pan et al 2020), analysis of bacteria (Kang et al 2020), and analysis of microplastics (Primpke et al 2020). Other common research topics revealed by title analysis included but are not limited to food quality, food production, food processing, food additive, food contamination, detection of food contaminants, food microbiology, environmental impact, as well as water, soil, animal, fish, meat, and dairy.…”
Section: A Scientometric Reviewmentioning
confidence: 99%
“…SERS spectra can give vibrational spectroscopic fingerprints from chemical and biological materials and therefore provide a comprehensive characterization tool to gain an understanding of the molecular structure [ 10 , 11 ]. Therefore, SERS offers high sensitivity and specificity in molecular identification and is a promising tool for the detection of adverse residues in food [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%